Determinan Penduduk Lanjut Usia Miskin di Daerah Istimewa Yogyakarta - Parwodiwiyono, Suparna (Jurnal Indonesia Sosial Sains, 2022)
Elderly population is someone who has reached the age of 60 years or more and some of them live in poverty. This study aims to look at the characteristics of elderly poverty in the Yogyakarta Special Region, both in terms of size and related determinants of elderly poverty. The research is based on secondary data from the March 2019 National Socio-Economic Survey. The descriptive analysis was followed by inferencing with the logistic regression method. Based on the Statistics Indonesia poverty line criteria and per capita calculations, it was found that the number of poor elderly people in the Yogyakarta Special Region was 96,412 people or about 17.4 percent of all elderly people in the area. If the poverty line rises to 1.2 times, the elderly poverty rate in the Yogyakarta Special Region will increase sharply to 27.4 percent. If we use the equivalent household member criteria, the percentage of poor elderly in the Yogyakarta Special Region gets a much smaller value. The statistical model shows that the area of residence, the highest education level of the elderly, the elderly jobs, social security with government contribution assistance recipients, and the number of household members, and age groups are important determinants of the poverty status of the elderly in the Yogyakarta Special Region. Specific policies are needed, especially increasing health insurance coverage for the poor elderly.